Contribution of Resistance Band and Single Leg Stand Training to Shooting Accuracy in Youth Soccer Athletes - Fachri Ananda Rezeki; Ibrahim Wiyaka (Jurnal Segar, 2026)
This study aimed to determine the effect of resistance band training and one-leg standing training on the shooting accuracy of SSB Harimau Tapanuli athletes at DR TD Pardede Stadium, Jl. Binjai KM 10.8, Purwodadi Village, Sunggal District, Deli Serdang Regency, North Sumatra. The research employed an experimental method using a one-group pretest-posttest design. The population consisted of 60 athletes, while the sample included 12 participants selected through purposive sampling based on specific criteria. Data collection was conducted using tests and measurements, including leg muscle strength tests, static balance tests, and shooting accuracy tests. The results showed an increase in all measured variables after the training program. The average leg muscle strength score increased from 39.125 in the pre-test to 52.875 in the post-test. Similarly, the average static balance score improved from 10.39 seconds to 14.88 seconds, while the average shooting accuracy score increased from 7.08 to 11.08. The regression analysis demonstrated that both leg muscle strength and static balance contributed positively to the improvement of shooting accuracy. The regression coefficient for leg muscle strength was 0.110, whereas the coefficient for static balance was 0.292, indicating that improvements in these variables can significantly enhance athletes’ shooting accuracy, both individually and simultaneously. Furthermore, the simultaneous test (F-test) revealed that the calculated F value (13.170) was greater than the F table value (4.26), with a significance value of 0.002 < 0.05. Therefore, it can be concluded that resistance band training and one-leg standing training significantly affect the shooting accuracy of SSB Harimau Tapanuli Deli Serdang athletes.